Néel transition in the multiferroic BiFeO 3 -0.25PbTiO 3 nanoparticles with anomalous size effect - Harijan P.K.; Singh A.; Upadhyay C.; Pandey D. (My University, 2025)
The role of size reduction on the structural parameters, antiferromagnetic transition temperature (T N ), and spin reorientation transition temperature of BiFeO 3 -0.25PbTiO 3 (BF-0.25PT) has been studied. Rietveld analysis using high resolution synchrotron x-ray powder diffraction data confirms that the space group of BF-0.25PT solid solutions is monoclinic Cc and not rhombohedral R3c for both bulk and nanocrystalline powders. This settles a longstanding controversy about the structure of these solid solutions toward the BiFeO 3 rich end of the morphotropic phase boundary in the BiFeO 3 -xPbTiO 3 system. Using magnetization and neutron powder diffraction data, we show that the Néel transition temperature (T N ) of BF-0.25PT increases from 445 K for bulk to 480 K for 150 nm particle size. This is in marked contrast to the scaling theories of phase transitions in finite size systems. We also show that the spin reorientation transition occurring below T N in bulk monoclinic compositions like BF-0.25PT is suppressed in the nanocrystalline samples of ∼150 nm particle size. Based on Rietveld refined structural parameters, we show that the asymmetry and non-linearity of the Fe-O-Fe superexchange pathways grow with decreasing particle size and that they exhibit a strong correlation with T N . We believe that the substantially enhanced Dzyaloshinskii-Moriya interaction with decreasing particle size as a result of asymmetric and non-collinear Fe-O-Fe superexchange pathways may be the key factor in raising the T N on decreasing the particle size. These observations present a new facet of type-I multiferroic materials, where superexchange pathways are intimately dependent on the ferroelectric distortion. © 2018 Author(s).